STATUS HUKUM DARI HARTA BENDA DAN ANAK YANG LAHIR DARI PERKAWINAN YANG TIDAK DILANGSUNGKAN SECARA AGAMA - Heru Tandoyo (CALYPTRA, 2014)
Research of Law Status of Property and Child Born from Non-Religious Marriage, if it were observed using Act Number 1, Year 1974 regarding Marriage, is count as a Putative Marriage. However, there is a solution or chance that the marriage that was not align with the Marriage Act becomes valid. That is by putting forward a petition to District Court to obtain an agreement with provision that marriage from both parties has fulfilled all clauses that have been arrange in Act of Marriage. With this, Writer is discussing the problem of the marriage status and its position based on property and child born from non-religious marriage law. Writer is also discussing about points included in the Marriage Act and applying it to the available cases, then looking for a win-win solution. The Writer has done the research by using Statute Approach, which is an approach that refers to Act Regulations. The methodology that is used in this report is normative juridical, which is a research of law by studying record or secondary data. The solution for the main problem of this report is by doing religious marriage prior to put forward an appeal to the District Court of Domicile from all parties to obtain an agreement from the District Court, so that the marriage becomes valid. Moreover, in regards of the problem of property and child born from putative marriage, the solution is achieved once the marriage is valid. All parties will be able to lodge another appeal to District Court of Domicile to obtain an agreement that property and child born from this marriage is also valid.